Targeted gene expression study of Salmonella enterica during biofilm formation on rocket leaves. (January 2016) - Doulgeraki, Agapi I.; Papaioannou, Maria; Nychas, George-John E.
Abstract: In the present study, the ability of Salmonella Typhimurium to form biofilm community on rocket leaves and rocket extract at 10 °C and 20 °C was investigated. This goal was achieved with the study of expression of genes associated with biofilm formation and other functional roles. The obtained results showed that Salmonella growth was inhibited when cultured in rocket extract (liquid and solid state) and when grew directly to rocket leaves. The observed inhibition might be attributed to nutrient starvation to the specific growth media because of plant leaves's variability, cell physiology and antimicrobial compounds of rocket. In addition, gene expression study using Real-Time PCR showed that biofilm was formatted on solid media, while the entrance and adhesion of the microorganism within the plant held more strongly through the stomata of the plant leaves. Furthermore, genes associated with managing stress situations were overexpressed at 20 °C. From these results, it is indicated that further studies are needed to better determine the survival and/or growth of the pathogen as "real" biofilm cells on plants. In addition, the study on development and gene expression of biofilm cells is necessary in order to eliminate the specific pathogen and reduce the food-borne diseases it causes. Highlights: Salmonella biofilm formation on rocket leaves and rocket extract was investigated. Expression of genes associated with biofilm formation was studied. Salmonella growth on rocket leaves and rocket extract was inhibited. Entrance and adhesion of Salmonella held more strongly through the stomata. Genes associated with managing stress situations were over-expressed.